MONITORING SYSTEM DESIGN OF TRACKING SYSTEM ON SOLAR PANEL FOLLOWING THE SUN ROTATION BASED ON INTERNET OF THINGS - Wardhana, Irdza; Priyatman, Hendro; Judiarto, Hilda (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2023)
In the field of energy, the sun is a large amount of energy and is still little utilized. Solar panels are a tool for utilizing solar energy into electrical energy. The average installation of solar panels is still static/fixed. Static solar panels cause the reception of sunlight energy to be less than optimal. To maximize the energy of sunlight, this solar panel is made dynamic or moved following the direction of sunlight. The monitoring process will be carried out based on the Internet of Things where the parameters to be measured are the value of voltage,current,power,solar panel temperature,and solar irradiation which will appear on the Blynk application via smartphone. Tests were conducted to determine the characteristics of the parameters measured between static solar panels and dynamic solar panels for 7 days. The maximum power value obtained by dynamic solar panels is better than the maximum power obtained by static solar panels, the largest average test value for 7 days from solar panels obtained a power value of 8.54 Watts and on static solar panels obtained a power value of 7.03 Watts. The position of the solar panel towards the sun, environmental conditions,weather conditions affect the value of the measured parameters.